Identification of Understanding of Disaster Preparedness in the School Environment - Azmi Khusnani; Rahmawati Husein; Adi Jufriansah; Ota Welly Jenni Thalo; Kartika Dewi Rahmawati; Mohammad Fitri; Colomeischi Aurora Adina (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
Flores Island is vulnerable towards natural disasters. Therefore, it requires an effective disaster warning ma-nagement. In this context, schools play an important role in disaster warning system. However, not all schools implement Disaster Risk Reduction (DRR) procedures effectively. Therefore, efforts are needed to improve disaster warning system among schools by integrating the three pillar principles, which include safe facilities, effective disaster management, and resilience education. This study aims to understand the state of school readiness in the Flores region and assess the extent to which these schools apply the three pillar criteria for school disaster warning system. The research method used is a qualitative descriptive ap-proach, with data collection through an open questionnaire distributed using Google Forms. The result showed that the locations of the respondent's schools are spread across the most disaster-prone areas of Flo-res, especially along the coastal areas. In addition, there are still many schools in the region that have diffe-rent levels of understanding and awareness regarding to disaster warning system. Based on that issue, the program for activating the disaster warning system in school area is very important to apply and can increase public awareness of disaster warning system. To achieve that idea, a collaboration between school commit-tees, external parties, and the Flores community is essential to strengthen the school infrastructure and to build an effective response towards potential disaster risks and threats.